The Prince Edward Islands : land-sea interactions in a changing ecosystem - Chown, Steven L.; Froneman, Pierre William (SUN PReSS, 2008)
CITATION: Chown, S.L. & Froneman, P.W. (eds). 2008. The Prince Edward Islands Land-Sea Interactions in a Changing Ecosystem. Stellenbosch: SUN PReSS. doi:10.18820/9781928357063. The original publication is available from AFRICAN SUNMeDIA - www.sun-e-shop.co.za Islands are typically studied because of their unusual terrestrial plant and animals life, because they form the breeding grounds for immense colonies of pelagic predators, and because they provide remarkable, open-air laboratories for understanding the structure and functioning of natural systems. The sub-Antarctic Prince Edward Islands are no exception. However, a great deal of attention has also been given to the way in which marine and terrestrial systems interact and influence each other’s dynamics, making the islands unusual. Indeed, Marion and Prince Edward Islands and their surrounding marine systems are amongst the most thoroughly investigated on the globe, and certainly hold the title for Southern Ocean. This book provides a modern, synthetic overview of what is known about the structure, functioning and interactions of marine and terrestrial systems at the Prince Edward Islands. Building on more than 50 years of biological, geological, meteorological, and oceanographic research, it demonstrates not only how inextricably linked marine and terrestrial systems at the islands are, but also how global environmental challenges, such as climate change, biological invasions, and over exploitation, are playing out at the regional and local levels in the Southern Ocean. The book also provides a rare insight into the history of the human presence on the islands, including the ways in which South Africa’s socio-political history has influenced practices at a remote sub-Antarctic research station, which has been occupied since the islands’ annexation in 1947/48. Publishers' version